2023
DOI: 10.1039/d2qo02046g
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic dehydrations for the Ritter reaction

Abstract: Ritter reaction is a powerful method for the synthesis of amides, however, photoinduced Ritter reaction of alcohol is rarely reported. We herein report a simple and additive-free photocatalytic dehydration method...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The photocatalytic amidation reaction has also been reported. In 2023, Bao et al [77] developed a photocatalytic dehydration of alcohol 102 to synthesize amides 103 (Scheme 24). The reaction uses 2,4,6-triphenylpyrylium tetrafluoroborate (PC1) as a catalyst, and benzyl alcohol and acetonitrile can produce amide after 16 h of blue light irradiation in a nitrogen atmosphere.…”
Section: Scheme 19 Synthesis Of Amide By Electrophotocatalytic Reactionmentioning
confidence: 99%
“…The photocatalytic amidation reaction has also been reported. In 2023, Bao et al [77] developed a photocatalytic dehydration of alcohol 102 to synthesize amides 103 (Scheme 24). The reaction uses 2,4,6-triphenylpyrylium tetrafluoroborate (PC1) as a catalyst, and benzyl alcohol and acetonitrile can produce amide after 16 h of blue light irradiation in a nitrogen atmosphere.…”
Section: Scheme 19 Synthesis Of Amide By Electrophotocatalytic Reactionmentioning
confidence: 99%
“…4 Simple alcohols are widely utilized as carbocation precursors in the Ritter reaction (Scheme 1b). 5 Recently, there has been an emphasis on developing catalytic Ritter-type C–H amidation for the selective synthesis of amides from alkanes, where the carbocation intermediates are generated by C–H bond oxidation (Scheme 1b). 6 However, these methods encounter certain challenges, including the use of excessive strong acids, transition metal reagents, high temperature, stoichiometric oxidants, and/or unwanted by-products.…”
mentioning
confidence: 99%
“…9 The coupling of amines with pre-activated carboxylic acids or carboxylic acid derivatives (esters, aldehydes, acyl halides and acid anhydrides) is an effective method for constructing amide bonds. [10][11][12][13][14][15][16][17][18] In recent years, alcohols, [19][20][21] olens, [22][23][24][25] and alkynes [26][27][28] have also been used as carboxylic acid substitutes to synthesize amides.…”
mentioning
confidence: 99%
“…It is worth noting that increasing the temperature does not improve the reaction efficiency, but reducing the temperature from 40 °C to room temperature only provides 20% of the product 3a (Table 1, entry 7-11). Subsequently, various bases including K 2 CO 3 , KHCO 3 , NaHCO 3 , KOAc, NaH 2 PO 4 , NaH, DMAP, and Et 3 N, were screened (Table 1, entries [12][13][14][15][16][17][18][19], and it was found that K 2 CO 3 was the most suitable base with a maximum yield of 93% (Table 1, entry 12). Furthermore, products 3a could not be obtained without the addition of base (Table 1, entry 20).…”
mentioning
confidence: 99%